The Impact of Micro-Influencers on Consumer Trust in Digital Business - Mujianto, Haryadi; Zakiah, Kiki; Yuningsih, Ani (Jogjakarta Communication Conference (JCC), 2025)
The development of digital technology has changed the landscape of business communication, especially social media-based marketing strategies. One growing trend is the use of micro-influencers, namely individuals with between 10,000 and 100,000 followers, who have high levels of engagement and are considered more authentic than macro-influencers or celebrities. This study aims to analyze the impact of micro-influencers on consumer trust in digital businesses, focusing on the factors that influence trust and how that trust impacts purchasing decisions. This study uses a quantitative method with data collection techniques through surveys. The main variables analyzed include authenticity, transparency of support, audience engagement, and brand loyalty. The results of the study show that micro-influencers have a significant influence on consumer trust, especially because they are considered more personal, honest, and transparent in providing product recommendations. The high level of interaction between micro-influencers and their audiences also increases emotional attachment and loyalty to the brands they promote. In addition, micro-influencer-based marketing strategies have proven to be more effective in building long-term relationships with consumers compared to traditional advertising or macro-influencers. These findings are expected to provide insight for businesspeople and marketers in developing more effective digital marketing strategies that are oriented towards consumer trust.